The composing process of Hong Kong children in primary schools - Tse, Shek Kam (1993)
Writing is the act of putting thoughts into visible print, a means of articulating and refining one's thinking and a means of communicating such thinking to others. In the past twenty years, a growing number of research studies have been concerned with elucidating the mental faculties, routines and sequences involved as people compose messages in writing representing thoughts in forms which they hope will be mutually understood by intended targets of the communication. Such research has been useful in illuminating ways in which writers can express themselves, and be taught to express themselves, in ways suitable to the task in hand. The bulk of such research has been concerned with English, and it seems to be presumed that the outcomes of such studies carry relevance for languages other than English. Equally, it seems to be presumed that the findings pertain to composers using English when it is a second language of state or a foreign language. This thesis explores in a modest way the validity of these presumptions using as subjects primary school age children from Hong Kong. The study is hence concerned with English, the world's premier international language, and Chinese, the world's most commonly used language. The thesis presents research into the composing processes in English and in Chinese employed by 18 primary school pupils in Hong Kong. It offers an in-depth study of the key subprocesses of generating, transforming, pausing and revising. The research was exploratory in nature and sought to gather evidence which might throw light on what happens when primary school pupils in Hong Kong compose in Chinese and in English. The strategy employed was a multiple case study approach. Subjects were asked to write two scripts, one in Chinese and one in English. Although the mother tongue of all the subjects is Cantonese, a dialect of Chinese, in school they are required to write either in Modem Standard Written Chinese or in English, the second language of Hong Kong. The subjects were given set tasks, either to write in a narrative or an expository style. The methods used to gather evidence and data were composing aloud and transcribing their utterances, video and audio-recorded observation, text analysis, on-task observational notes, cued-recall interviews and retrospective reports. The subjects' reflections were cued by being shown the video recordings.